Remote Control - l'atelier documentaire (France, 2015)
Tehran, June 2013. The Iranians are preparing to elect the new President of the Islamic Republic. Massed in front of their TV, they comment the presidential campaign broadcast by national channels. In the privacy of their homes, facing the images relayed by satellite feed, state propaganda, images of the West, Egypt or Syria, women and men freely talk about their hopes and fears.
Verzio Film Festival Submission
Keywords: Documentary films